Access to cyclopropanes with geminal trifluoromethyl and difluoromethylphosphonate groups - Hajdin, Ita; Pajkert, Romana; Keßler, Mira; Han, Jianlin; Mei, Haibo; Röschenthaler, Gerd-Volker (Beilstein Journal of Organic Chemistry, 2023)
A synthetic route to the bench-stable fluorinated masked carbene reagent diethyl 2-diazo-1,1,3,3,3-pentafluoropropylphosphonate, bearing a trifluoromethyl and a difluoromethyl group is reported for the first time. Its application in CuI-catalyzed cyclopropanation reactions with aromatic and aliphatic terminal alkenes under mild reaction conditions is demonstrated. In total, sixteen new cyclopropanes were synthesized in good to very good yields.
Keywords: alkenes; cyclopropanation; diazo compounds; difluoromethylphosphonate; DFT calculations